Non-invasive assessment of vascular alteration using ultrasound. Issue 1 (December 2015) - Yang, Woo-In; Ha, Jong-Won
Abstract It is well known that arterial function relates to cardiovascular morbidity and mortality. The noninvasive technology for the assessment of arterial function has developed as the importance of prevention of early cardiovascular disease has been emphasized. Over 2-D and Doppler echocardiography, speckle-tracking echocardiography has emerged as a valuable ultrasound imaging technique that allows for an objective and quantitative evaluation of global and regional myocardial function. Recently, several studies have extended its applicability beyond cardiac chambers, such as artery. Measurement of carotid arterial strain with speckle tracking ultrasound has been shown to be feasible and reliable. This review describes the new ultrasound techniques to assess arterial function and their clinical implications.